Working memory and musical competence of musicians and non-musicians. (November 2013) - Hansen, Mads; Wallentin, Mikkel; Vuust, Peter
Musical ability has been found to be associated with an enhancement of verbal working memory. In this study, we investigated whether this effect would generalize to visual-spatial working memory as would be expected if the effect were driven by general intelligence. We administered the WAIS-III Digit Span; the WMS-III Spatial Span; and the Musical Ear Test (MET), a forced-choice same/different listening task measuring musical ability, to non-musicians, amateur musicians, and expert musicians. Expert musicians significantly outperformed non-musicians on the Digit Span. Additionally, Digit Span Forward scores were found to be correlated with MET total scores and with scores on the rhythm subtest of the MET. No between-group differences were found on the Spatial Span.